Development of a methodology to determine ventilation parameters with CFD simulations in airway tree geometry obtained from CT scans (2021)
Nowadays, the principle on which the distribution of the pulmonary ventilation (V) perfusion (Q) index is based and proposed states the main force that determines this rate is gravity. From this, it was established that the behavior of this index is modified depending on how close the lung lobe of interest is to the lung base. However, there is compelling evidence to consider that the behavior of this variable is not governed solely by these laws and that within the lung volume there are random regions with ideal values to carry out gas exchange effectively and these do not obey the previously established trends. A real threedimensional model of the lung airway architecture was obtained from CT-scans and a computational flow dynamics study was performed through these meshed geometries with the objective of determining an in-silico approximation to the real volumetric air flow values in the different lung regions or determined lung lobes, which have a direct repercussion on the index of interest. These values are meant to be parameters inputs to be used in a previously proposed mathematical model whose result illustrates this V / Q index zoning for ideal gas exchange.